Integrating Quranic Spiritual Pedagogies Constructs A Balanced Moderate Identity: Mengintegrasikan Pedagogi Spiritual Al-Qur'an Membangun Identitas Moderat Yang Seimbang - Marwal Blantara Susetyo; Aceng Kosasih; Aulia Tegar Wicaksono; Mhd. Aksaril Huda Ritonga; Muhammad Fahri Ali Husaeni (Halaqa: Islamic Education Journal, 2026)
General Background The rapid advancement of digital technology during the Society 5.0 era paradoxically correlates with moral degradation, identity crises, and mental health challenges among the younger generation. Specific Background Islamic educational traditions address these issues by combining soul purification with intellectual development, utilizing practices like Quranic recitation and spiritual meditation that show promise in reducing anxiety while building resilience. Knowledge Gap However, existing literature remains fragmented across neuroscience, psychological well-being, and pedagogical curriculum domains, lacking a systematic framework that unites these dimensions. Aims This study synthesizes empirical findings regarding the roles of Tilawah, Tazkiyah, and Ta'lim in holistic human personality development using a Systematic Literature Review based on the PRISMA 2020 protocol, analyzing 15 Scopus-indexed articles from 2021 to 2025. Results The findings reveal that Tilawah contributes to mental stability and cognitive focus, Tazkiyah facilitates emotional regulation and character formation, while Ta'lim strengthens intellectual maturity and inclusive religious understanding. Unifying these three elements creates a comprehensive spiritual pedagogy framework. Novelty This research integrates modern empirical findings to formulate the conceptual model of a Wasathan personality, emphasizing equilibrium among spiritual awareness, moral integrity, and intellectual maturity. Implications This conceptual model contributes theoretically to the advancement of contemporary Islamic education, offering a holistic pedagogical strategy to overcome modern moral obstacles while recommending future quasi-experimental studies to measure character transformation objectively. Highlights Tilawah yields mental stability while promoting cognitive focus. Tazkiyah facilitates emotional regulation alongside resilient character formation. Ta'lim strengthens intellectual maturity plus inclusive religious understanding. Keywords Spiritual Pedagogy; Wasathiyah Personality; Systematic Literature Review; Character Formation; Islamic Education .